2014
DOI: 10.1590/s1516-8913201402377
|View full text |Cite
|
Sign up to set email alerts
|

Activity of encapsulated Lactobacillus bulgaricus in alginate-whey protein microspheres

Abstract: In this work, alginate-whey protein was used as wall materials for encapsulating

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 25 publications
0
24
1
Order By: Relevance
“…Soy protein isolate-alginate microspheres were prepared according to previous works (Pan et al 2013;Shi et al 2013a, b;Chen et al 2014;Tang et al 2013Tang et al , 2015. Briefly, E. faecalis HZNU P2 was mixed with sodium alginate and soy protein isolate.…”
Section: Encapsulation Of E Faecalis Hznu P2 In Soy Protein Isolate-mentioning
confidence: 99%
See 4 more Smart Citations
“…Soy protein isolate-alginate microspheres were prepared according to previous works (Pan et al 2013;Shi et al 2013a, b;Chen et al 2014;Tang et al 2013Tang et al , 2015. Briefly, E. faecalis HZNU P2 was mixed with sodium alginate and soy protein isolate.…”
Section: Encapsulation Of E Faecalis Hznu P2 In Soy Protein Isolate-mentioning
confidence: 99%
“…It can provide various health benefits, including preventing diarrhoea, balancing intestinal microflora, stimulating the immune system, improving lactose intolerance, etc. (Rajam et al 2012;Dong et al 2013;Khan et al 2013;Pan et al 2013;Shi et al 2013a, b;Chen et al 2014). However, it has been reported that many factors, such as low pH, hydrogen peroxide, dissolved oxygen, and storage temperature can affect the viability of probiotics (Champagne et al 2011;Rajam et al 2012;Dong et al 2013;Chen et al 2014).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations